Penerapan Budaya 5S (Salam, Senyum, Sapa, Sopan, dan Santun) sebagai Penguatan Pendidikan Karakter di SDN 6 Mataram - Hidayat, Muhammad Hazrul; Dita, Ni Nyoman; Serli, Serli; Septi, Widya; Sagira, Adella (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
The 5S culture (Salam/Greeting, Senyum/Smiling, Sapa/Greeting by name, Sopan/Politeness, and Santun/Courtesy) plays a vital role in shaping students' character in elementary schools. This study aims to examine the implementation of the 5S culture at SDN 6 Mataram as part of fostering a positive and child-friendly school environment. The method used was literature study, referring to recent research findings. The results showed that practicing the 5S culture improved students’ social ethics, reduced peer conflicts, and created a conducive learning atmosphere. This article emphasizes the importance of consistent involvement from teachers, school principals, and teaching-assistance students in instilling 5S values. These findings are expected to serve as a reference for other schools to foster positive culture through character-based habits in elementary education.